A Decade of Neuromarketing in Consumer Preferences: A Bibliometric Analysis - Nizar Fauzan (Relevance: Journal of Management and Business, 2026)
The study aims to provide a decade-long bibliometric and visualization analysis of trends in neuromarketing and consumer behavior. The examination of publication trends and emerging topics. This study uses advanced visualization tools to highlight key developments and thematic shifts in neuromarketing. Employing bibliometrics on 633 documents indexed in the Scopus database, limited to 2010–2025. This study focuses on neuromarketing research that influences consumer behavior. Biblioshiny (Bibliometrix package in R-Studio) and VOSviewer were utilized to map co-authorship networks, citation networks, and keyword co-occurrences. These facilitated automated visualization of the research structure across journals, authors, countries, citations, co-citations, and thematic clusters. The study relied heavily on the Scopus database over the past decade. Future studies suggest that the database include a broader range of neuromarketing studies to offer a constructive of the discipline's evolution and trends. Neuromarketing can more effectively predict consumer behavior. Companies and marketers can use neuromarketing to refine their strategies, ensuring they align with consumer preferences and behavior. This could lead to marketing approaches that engage target consumers more deeply, enhancing satisfaction and loyalty. Consumer behavior benefits but raises ethical concerns regarding consumer manipulation. The study revealed a growing need for ethical guidelines and standards in neuromarketing practices to protect consumers. Establishing ethical frameworks for the neuromarketing practices. This study's bibliometric tools and methods map the evolution and themes of neuromarketing, offering insight into its impact on consumer behavior. This implementation highlights the field's growth and trends, laying the foundation for future research directions.